Citizen of Zimbabwe : Conversations with Morgan Tsvangirai. - Chan, Stephen (Weaver Press, 2010)
Morgan Tsvangiraiís appointment as Zimbabweís Prime Minister in 2009 followed many yearsí leadership of the Zimbabwe Congress of Trades Unions and the Movement for Democratic Change. How has that experience equipped him for high national office? Does he have the personal, intellectual and political qualities required to be President? In July 2004, as he was awaiting the verdict in his treason trial, Tsvangirai spent several days in conversation with Stephen Chan. Chan was concerned to find out if Tsvangirai was more than ëmerely a charismatic leader of the oppositioní; if he had ëhis own intel.